2020
DOI: 10.1177/0846537119888380
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Diffusion-Weighted MRI Compared to 18 FFDG PET/CT in Initial Staging and Therapy Response Assessment of Hodgkin Lymphoma in Pediatric Patients

Abstract: Purpose: The aim of our study was to compare whole-body diffusion-weighted MRI (WB-DWI-MRI) to fluoro-2-deoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) in the assessment of initial staging and treatment response in pediatric patients with Hodgkin lymphoma. Materials and Methods: This prospective study comprised 11 children with Hodgkin lymphoma. Whole-body DWI-MRI and FDG-PET/CT were obtained at baseline and after 2 cycles of chemotherapy. Two radiologists measured the apparent diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…However, it contains ionizing radiation. Nevertheless, in a study comparing magnetic resonance imaging and PET CT, PET CT was shown to be more sensitive in staging at the time of diagnosis and evaluating the response to treatment (20). We used PET CT for staging and evaluation of response to treatment in all of our patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, it contains ionizing radiation. Nevertheless, in a study comparing magnetic resonance imaging and PET CT, PET CT was shown to be more sensitive in staging at the time of diagnosis and evaluating the response to treatment (20). We used PET CT for staging and evaluation of response to treatment in all of our patients.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, not all study results support the use of whole-body DWI for pediatric lymphoma staging. Thus, a study of Shapira-Zaltsberg and colleagues with focus on pediatric HL highlights the superiority of PET/CT at initial staging and assessment of therapy response [ 66 ]. However, at comprehensive [ 18 F]FDG PET/MRI staging of pediatric lymphoma patients, whole-body DWI seems to have no beneficial effect for staging [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a significant reduction in ADC values in most patients with LCH may provide some clues for the differential diagnosis of other tumors, such as lymphoma. 21 …”
Section: Discussionmentioning
confidence: 99%
“…The lack of a significant reduction in ADC values in most patients with LCH may provide some clues for the differential diagnosis of other tumors, such as lymphoma. 21 The skeletal system is the most frequently involved system in LCH. Most of the images show bone destruction with soft tissue mass formation, surrounding soft tissue exudation and edema, and compression of the adjacent spinal cord.…”
mentioning
confidence: 99%